Seguro defeso: Diagnóstico dos problemas enfrentados pelo programa - André Gambier Campos; José Valente Chaves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– With plenty of merits, Seguro Defeso (a kind of unemployment benefit) is a program located at the confluence of social and environmental policies, defined after the Constitution of 1988 in Brazil. It supports artisanal fishermen, unable to subsist based on their work during certain period of the year. Furthermore, it offers some protection to aquatic species, comprising the country's ecosystem. Despite the relevance of its social and environmental roles, Seguro Defeso faces several problems nowadays, related to the fact that it benefits groups that apparently are not artisanal fishermen (or even fishermen). This text provides evidences about those problems, focusing at discrepancies between fishermen and beneficiaries of Seguro Defeso, as well as at the financial costs involved in those discrepancies.
Keywords: I38; J08; J65; 330; social policies; environmental policies; artisanal fishermen